INTERACTIVE METHODS FOR THE DEVELOPMENT OF THE INTELLECTUAL CULTURE OF FUTURE TEACHERS ON THE BASIS OF INTEGRATIVE EDUCATION (Scientific journal of the Fergana State University, 2023)
In the article, the rapid scientific and technical development in the world at the present time requires paying serious attention to education, especially the higher education system, the future prospects of any country depend on the high intellectual potential of its competitive personnel, the future personnel Pedagogical aspects of the rational use of philosophy in the formation and development of intellectual culture are discussed.